Synthesis, Biological Evaluation and Docking Studies of Quinoline Pyrazolyl‐Chalcone Hybrids as Anticancer and Antimicrobial Agents. Issue 42 (10th November 2021) - Kamra, Nisha; Rani, Suman; Kumar, Devinder; Singh, Ajeet; Sangwan, Payare L.; Singh, Shashank K.; Thakral, Samridhi; Singh, Vikramjeet
Abstract: A series of new quinoline pyrazolyl‐chalcone hybrids (4 a –4 s ) was obtained from 4‐acetyl‐5‐methylquinolylpyrazole and aromatic aldehydes and the structure of these hybrids were established with the help of FTIR, 1D NMR ( 1 H and 13 C), 2D NMR and HRMS data. The anticancer potential of selected quinoline pyrazolyl‐chalcone hybrids was evaluated against colon cancer (HT‐29, HCT‐116), lung cancer (A549), and prostate cancer (PC‐3) cell lines. ( E )‐1‐(5‐Methyl‐1‐(4‐methylquinolin‐2‐yl)‐1 H ‐pyrazol‐4‐yl)‐3‐(2, 4, 6‐trimethoxyphenyl)prop‐2‐en‐1‐one (4 j ) displayed good cytotoxicity with IC50 values of 5.4, 3.2 and 2.8 μM against HT‐29, A549, and PC‐3 cancer cell lines, respectively. The antimicrobial potential of quinoline pyrazolyl‐chalcone hybrids was tested against three bacterial strains ( B. subtilis, S. aureus and E. coli ) and two fungal strains ( A. niger and C. albicans ). ( E )‐1‐(5‐Methyl‐1‐(4‐methylquinolin‐2‐yl)‐1 H ‐pyrazol‐4‐yl)‐3‐(3‐nitrophenyl)prop‐2‐en‐1‐one (4 r ) exhibited significant activity against Gram positive bacteria ( B. subtilis and S. aureus) and fungal strains with MIC value of 15.6 μM. Molecular docking analysis was conducted to determine the binding interactions of quinoline pyrazolyl‐chalcone hybrids with their respective biochemical targets viz . Epidermal growth factor receptor tyrosine kinase (EGFR), Thymidylate kinase (TMK) and C. albicans N‐myristoyltransferase. Abstract : Synthesis of quinoline pyrazolyl‐chalcone hybrids have been accomplished and evaluated for in vitro anticancer activity against different cell lines and microbial strains. ( E )‐1‐(5‐Methyl‐1‐(4‐methylquinolin‐2‐yl)‐1 H ‐pyrazol‐4‐yl)‐3‐(2, 4, 6‐trimethoxyphenyl)prop‐2‐en‐1‐one displayed cytotoxicity with IC50 values of 5.4, 3.2 and 2.8 μM against HT‐29, A549, and PC‐3 cancer cell lines, respectively. ( E )‐1‐(5‐Methyl‐1‐(4‐methylquinolin‐2‐yl)‐1 H ‐pyrazol‐4‐yl)‐3‐(3‐nitro phenyl)prop‐2‐en‐1‐one exhibited significant activity against bacterial and fungal strains with MIC value of 15.6 μM. The binding interactions of hybrids with their respective biochemical targets were determined by molecular docking analysis.